Current State and Recent Changes of glaciers in the Patagonian Andes (~37 °S to 55 °S) - Ruiz, Lucas Ernesto; Pitte, Pedro Miguel; Rivera, Andres; Schaefer, M.; Masiokas, Mariano Hugo
This chapter addresses the distribution and characteristics of the Patagonian glaciers together with their recent changes and hydrological implications. Recently published national glacier inventories for the Andes between ca. 37 °S and 55 °S indicate that this region contains 24,000 ice masses covering ca. 26,100 km2. This includes the Southern Patagonia Icefield (SPI), the largest ice mass of the Southern Hemisphere outside Antarctica. The region also includes several thousand smaller ice masses, such as mountain glaciers, valley glaciers, rock glaciers, and perennial snowfields, which collectively are crucial water resources to sustain nature contributions to people, socioeconomic activities, and hydropower generation. Recent findings in mass balance and ice dynamics along the Patagonian Andes highlight the processes behind the mass change and differential response of glaciers to climate change. Although most glaciers have experienced considerable thinning and recession in recent decades, they have not responded in the same manner to climate change. Ice-dynamic processes, such as calving, drive mass change of larger Patagonian glaciers. However, ice melt increases, and snowfall depletion have been attributed as the main cause for the shrinkage of the smaller ice masses. It is expected that glacier retreat will continue impacting runoff and glacier-related hazards. Modeling studies suggest strongest impacts due to this recent ice mass loss can be expected, particularly during the dry season. In concordance with the increase in the number and size of proglacial lakes, there has been an increase in the magnitude and frequency of glacial lake outburst floods in the Patagonian Andes. Fil: Ruiz, Lucas Ernesto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. ...